The Rise of Student Suicides due to Lack of Social Support - Eka Sayekti Setyaningrum; Erin Wahyuni; Erni Mulyanie (Journal of Social Studies Education and Humanities Research, 2026)
Suicide among university students has become an increasingly important public health and social concern due to its association with psychological distress and inadequate social support. This study aims to examine the factors contributing to suicide among university students, analyze the relationship between social support and suicidal behavior, and identify effective prevention strategies. A qualitative approach using a narrative literature review was employed by synthesizing evidence from national scientific journals and relevant academic literature. The findings reveal that suicide is influenced by multiple interconnected factors, including family conflict, academic pressure, loneliness, interpersonal problems, and mental health disorders. Among these factors, inadequate social support from family, peers, and educational institutions emerged as a significant predictor of suicidal ideation. Guided by Durkheim's theory of social integration, the study demonstrates that weak social connectedness increases students' vulnerability to suicide. Strengthening family relationships, peer support, university counseling services, and mental health education are essential strategies for suicide prevention. These findings emphasize the importance of developing comprehensive social support systems to promote psychological well-being and reduce suicide risk among university students.